DESENVOLVIMENTO DE BEBIDA MISTA DE SORO DE LEITE COM TEOR DE LACTOSE REDUZIDO E EXTRATO HIDROSSOLÚVEL DE SOJA - Gregianin, Dóris de Oliveira (2014)
The increased incidence of cardiovascular disease and various cancers have been the cause of searching for changing habits in a large portion of the population, seeking the physical activity in conjunction with the consumption of healthier foods with higher nutritional content. Considering the high biological value of the proteins of sweet whey and the recognized effect in reducing risk of cardiovascular disease of soy protein, the aim of this study was to develop a mixed chocolate-soluble soybean extract dissolved in sweet whey. The different proportions of carrageenan stabilizers, pectin and tapioca starch were defined by the experimental design of mixtures simplex centroid. By optimizing the response surface was definitely the best formulation in relation to the physic-chemical and sensory parameters. The simultaneous optimization of response variables indicated that the optimal formulation should contain 46% carrageenan and 54% pectin and 0% starch, with a desirability index of 0.929. The formulation indicated for the desirability function was made with water soluble soy extract dissolved in sweet whey and; on sweet whey with reduced lactose content. Serum was hydrolyzed by the action of lactase from Kluyveromyces lactis yeast enzyme at a concentration of 2500 NLU / L in reaction 4 hr at 37 ° C. The sensory attributes were evaluated by nine points hedonic scale and attitude scale in purchase intent. For overall impression, the formulations presented average value of 7.11 ±1.09, while purchase intent the average value was 3.99 ± 1.28, and the multiple regression models proved to be predictive. The most widely accepted formulations were those who had lower viscosity and instrumental containing pectin in its constitution. The results obtained indicate that the combination of sweet whey and soy aqueous extract is a viable option for the preparation of a chocolate beverage. It was also observed that the use of cassava starch as a thickener does not interfere negatively on the rheological and sensory characteristics and; that the combined carrageenan and pectin concentrations defined predictive model ensures greater acceptability of the product.